Kepekaan Multibudaya Bagi Konselor Dalam Layanan Konseling - Agung Nugraha; Dewang Sulistiana (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2017)
Multicultural sensitivity both theoretical and empirical needs to be owned by counselors in the counseling service. Multicultural sensitivity is important in the counseling process because of its multicultural sensitivity counselor at counseling services can be predicted to be more effective. Counselors are required to have a multicultural sensitivity as access to better know, understand and appreciate the whole cultural experience that is owned by the counselee as well as exploring the potential counselee with a fixed packing uniqueness. The counselor with a keen sensitivity better understand and appreciate the cultural bias between the counselor and counselee which is predicted to be able to direct the counselee to develop optimally